Avaliação ambiental do setor calçadista sob a ótica da gestão de resíduos sólidos - Silva, Adriana Hoenisch da (Universidade do Vale do Rio dos Sinos, 2016)
Concerning the growing and effective worry for the environment with the use of non-renewable resources, the management of reusing and recycling, and not least, industrial waste generation has been the interest of research and projects. The footwear product uses in its manufacturing process several types of materials and natural resources, thus presenting as an interesting source of the use of environmental tools opportunities and case studies to reduce the environmental impacts generated by this production process. However, environmental gains achieved in production it has been overtaken by the negative impact of the considerable increase in footwear products demand for reflecting an increase of waste generation. To perform the environmental assessment and projection management of industry waste by evaluating lifecycle, this paper conducted a survey, by mapping and quantifying of industry waste to evaluate waste management opportunities. From a mapping and survey of industries located in the main footwear regions in the state of Rio Grande do Sul and its manufacturing process, there was the identification of the main materials used and waste generated, as well as its destination. From the data obtained from this survey, and also an analysis by a dismantling of shoe models available to inventory the materials used to build inventory was made of solid waste by means of block diagram with the main inputs, steps and outputs of the manufacturing process. To perform the evaluation of inventory life cycle (LCIA) considered a comprehensive analysis of the industry, in general scenarios of production, considering the information obtained from questionnaires applied in business, the analysis of data footwear and literature. As LCIA results, it was found that the female footwear manufacturing process made of leather results in waste of 28,6% of raw material and manufacturing the female shoe made of synthetic results in 18,1% of raw waste textile material. This data collection was used to build an inventory and to develop and LCIA, to identify and evaluate the environmental waste management opportunities for the footwear sector. As a result, it were observed the waste management opportunities through industry cooperatives, the need to emphasize the management in the raw materials use in order to minimize waste generation, to spread the idea of ecodesign for the manufacture of footwear to from the waste generated. There are studies and products using this trend promoting efforts with industry suppliers to ensure the environmental performance of footwear, the conscious use of natural resources and inputs. The results also show that the destination given to the industrial solid waste is most external recycling (86,67%), disposal to landfills (33,33%) and also destination for co-processing (26,67%).
Keywords: Calçado; Avaliação de inventário do ciclo de vida; Gestão; Resíduos; Footwear; Assessment of the life cycle inventory; Management; Waste; ACCNPQ::Engenharias::Engenharia Civil